1980
DOI: 10.1113/jphysiol.1980.sp013094
|View full text |Cite
|
Sign up to set email alerts
|

Swelling studies of bovine corneal stroma without bounding membranes.

Abstract: SUMMARY1. The swelling characteristics of demembranated bovine corneal stroma were studied as a function of time and of the pH and ionic strength of the bathing solution.2. Compared with other pH values, the stroma swelled least near pH 4. 3. In the pH range 6-10, increasing the pH resulted in an increase both in the rate of swelling and in the hydration reached in a given time.4. At pH 2 and 4, a final constant value of hydration was attained. At higher pH values no such equilibrium was attained when the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 33 publications
6
52
0
1
Order By: Relevance
“…In cornea, a substantial part of the fixed net negative charge on the proteins arises from immobilized anions (probably largely chloride ions) trapped in potential wells or otherwise fixed to the protein surfaces (Elliott, 1980;Elliott et al 1980). Hodson et al (1992) have confirmed that transient chloride binding is a large contributory factor to corneal stromal swelling in the ox in the physiological regime, showing that the model described here is reasonable.…”
Section: Ttsupporting
confidence: 48%
“…In cornea, a substantial part of the fixed net negative charge on the proteins arises from immobilized anions (probably largely chloride ions) trapped in potential wells or otherwise fixed to the protein surfaces (Elliott, 1980;Elliott et al 1980). Hodson et al (1992) have confirmed that transient chloride binding is a large contributory factor to corneal stromal swelling in the ox in the physiological regime, showing that the model described here is reasonable.…”
Section: Ttsupporting
confidence: 48%
“…The decrease in thickness in the human sclera after enzymetreatment could result from an overall loss of water with s-GAG degradation. The amount and type of negative ionic charges determine the scleral capacity for water absorption through charge [29] and osmotic [30][31][32] effects. However, the water absorption capacity of the tissue is also limited by the collagen interfibrillar spacing, itself governed by GAG-GAG charge repulsion [40] and GAG-GAG anti-parallel interactions [41].…”
Section: Discussionmentioning
confidence: 99%
“…If a small correction for hydration is included (Elliott and his coworkers assumed a physiological hydration of 3 4, whereas we used our measured physiological hydration of 3 2) the correspondence of the independently determined values for the fixed stromal charge is even closer. It appears that Donnan theory predicts accurately intrastromal electrical potential (Elliott, 1980), free swelling rates of stroma in saline (Elliott, Goodfellow & Woolgar, 1980) and corneal gel pressure measured by osmometry (current study) over a wide range of corneal hydrations. The theory accounts quantitatively for all the observed properties of corneal swelling except for one important group of exceptions, which all concern the measurement of corneal swelling pressure by mechanical methods.…”
Section: Discussionmentioning
confidence: 99%
“…1) then weight equilibrium was not attained, and even though the preparation might show an initial tendency to deturgesce, eventually tissue weight gain was progressive. In the whole-corneal preparations, where equilibrium was attained, the natural tendency of cornea to swell in saline (Elliott, Goodfellow & Woolgar, 1980) is balanced by the osmotic pressure generated by the non-penetrating solute (PEG 1OK) in the bathing solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation